Formation and IR spectrum of monobridged Si2H4 isolated in solid argon - Lin, Shu-Yu; Chou, Sheng-Lung; Lin, Meng-Yeh; Huang, Wen-Jian; Huang, Tzu-Ping; Wu, Yu-Jong (The Journal of chemical physics, 2020)
The infrared (IR) spectrum of monobridged Si2H4 (denoted as mbr-Si2H4) isolated in solid Ar was recorded, and a set of lines (in the major matrix site) observed at 858.3 cm−1, 971.5 cm−1, 999.2 cm−1, 1572.7 cm−1, 2017.7 cm−1, 2150.4 cm−1, and 2158.4 cm−1 were characterized. The species was produced by the electron bombardment of an Ar matrix sample containing a small proportion of SiH4 during matrix deposition. Upon photolysis of the matrix samples using 365 nm and 160 nm light, the content of mbr-Si2H4 increased. The band positions, relative intensity ratios, and D-isotopic shift ratios of the observed IR features are generally in good agreement with those predicted by the B3LYP/aug-cc-pVTZ method. In addition, the photochemistry of the observed products was discussed.